Development and Validation of the Bystander Engagement Scale for Witnessed Intimate Partner Violence: A South Korean Version - Park, Sihyun (Journal of interpersonal violence, 2024)
Bystanders play a crucial role in assisting and rescuing victims of intimate partner violence (IPV) or sexual assault, thereby preventing further harm. Consequently, an increasing amount of research has focused on improving bystander interventions in such situations. While many existing scales that measure bystanders’ willingness to intervene and their behaviors are likely tailored to Western settings and primarily focused on preventing sexual assaults, pursuing diversity to make these scales applicable to a variety of contexts is necessary. This study aimed to develop and validate a scale from South Korean samples that measure the likely level of bystander engagement in witnessed IPV situations, named the Bystander Engagement Scale for Witnessed Intimate Partner Violence (BESW-IPV). Preliminary items, developed to describe various IPV situations that a bystander might witness, underwent content validity testing through expert review and cognitive focus group interviews. Afterward, the scale was administered to 311 participants from the target population in South Korea. The scale’s factor structure was assessed through exploratory factor analysis (EFA) and confirmed through confirmatory factor analysis (CFA). The reliability and validity were rigorously assessed. The final version of the BESW-IPV comprised 28 items. Through EFA, “direct IPV indicators” and “indirect IPV indicators” were identified. Together, these factors accounted for 76.10% of the total variance. CFA affirmed that the final model offers an acceptable fit. The scale’s convergent and discriminant validities were also well established. The Cronbach’s alpha and the McDonald’s omega values were 0.98 and 0.99, respectively. In contrast to many existing tools that measure bystander intervention predominantly within the confines of Western educational settings, we believe that the BESW-IPV can be applied in broader contexts, especially in patriarchal environments. Further research is required to translate and validate this tool in different cultural contexts.